Analisis Skala Produksi Usahatani Jagung Pipil - Nanda Rosyita; M. Nasir Ismail; Khumaira Khumaira (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
Corn (Zea mays, Linn) is an industrial raw material and animal feed, Corn is classified as a strategic commodity because it meets the criteria, among others, has an influence on the price of other food commodities and has bright prospects. The increasing demand for maize in the country is closely related to the development of the food and feed industry. Therefore, efforts to increase maize production need to receive greater attention. Increased production can also still be pursued through improved harvest and post-harvest handling. The purpose of the study was to determine how much income and scale of production (returns to scale) on pipil corn farming in Teuladan Village, Seulawah Valley District, Aceh Besar Regency. The research method is the "Surve Method" with the "Simple Random Sampling" technique of 29 farmers. Income analysis method analyzed using π =TR-TC, and production scale analysis using multiple liner regression analysis with the Cobb-Dauglass Production Function Model. The results showed an average income value of 20,753,700. which means that peeled corn farming in the research area can generate income and is feasible. And based on the Return to scale (RTS) analysis of pipil corn farming in the research area, the result is 10.923 (Table 13), in the RTS analysis it can be said that the production of pipil corn farming is in a condition of increasing output scale (Incresing return to scale), because the sum of the values of the coefficients of the production factors is more than one (∑β> 1). This means that by adding a certain amount of input, the corn farm can achieve full efficiency.